Importance of lymph node immune responses in MSI-H/dMMR colorectal cancer - Koji Inamori; Yosuke Togashi; Shota Fukuoka; Kiwamu Akagi; Kouetsu Ogasawara; Takuma Irie; Daisuke Motooka; Yoichi Kobayashi; Daisuke Sugiyama; Motohiro Kojima; Norihiko Shiiya; Shota Nakamura; et al. (JCI Insight, 2021)
Patients with colorectal cancers (CRCs) generally exhibit improved survival through intensive lymph node (LN) dissection. However, recent progress in cancer immunotherapy revisits the potential importance of regional LNs, where T cells are primed to attack tumor cells. To elucidate the role of regional LN, we investigated the immunological status of nonmetastatic regional LN lymphocytes (LNLs) in comparison with those of the tumor microenvironment (tumor-infiltrating lymphocytes; TILs) using flow cytometry and next-generation sequencing. LNLs comprised an intermediate level of the effector T cell population between peripheral blood lymphocytes (PBLs) and TILs. Significant overlap of the T cell receptor (TCR) repertoire was observed in microsatellite instability–high/mismatch repair–deficient (MSI-H/dMMR) CRCs with high tumor mutation burden (TMB), although limited TCRs were shared between nonmetastatic LNs and primary tumors in microsatellite stable/MMR proficient (MSS/pMMR) CRC patients with low TMB. In line with the overlap of the TCR repertoire, an excessive LN dissection did not provide a positive impact on long-term prognosis in our MSI-H/dMMR CRC cohort (n = 130). We propose that regional LNs play an important role in antitumor immunity, particularly in MSI-H/dMMR CRCs with high TMB, requiring care to be taken regarding excessive nonmetastatic LN dissection in MSI-H/dMMR CRC patients.